Analysis of Heat Sink Modelling Performance - Tarvydas, P.; Noreika, A.; Staliulionis, Z. (Elektronika ir Elektrotechnika, 2013)
With increasing complexity of electronic components and their systems, their cooling solutions become an important issue, and heat sinks are the most widely applied solution in industry. Theoretical, experimental and numerical methods can be used to determine a heat sinks thermal performance. Finite element method is probably the most suitable numerical technique to simulate thermal fields of heat sinks. The advantages of finite element modelling and analysis of heat sinks are discussed. Thermal modelling of heat sink mounted inside air channel was accomplished using finite element analysis software COMSOL. Algorithm for heat sink model building was offered. Finite element mesh generation and problem solution performance was evaluated using created algorithm. Performance evaluation results are presented. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3695